2005
DOI: 10.1016/j.polymer.2005.07.074
|View full text |Cite
|
Sign up to set email alerts
|

Ability of nitrones of various structures to control the radical polymerization of styrene mediated by in situ formed nitroxides

Abstract: The ability of several nitrones to control the radical polymerization of styrene at 110 °C has been investigated by high-throughput experimentation. The nitrone/free radical initiator pair dictates the structure of the nitroxide and the alkoxyamine formed in situ, which determines the position of the equilibrium between the active and the dormant species operating in the nitroxide-mediated polymerization. For the styrene polymerization to be controlled, the nitrone must be reacted with 2,2′-azo-bis-isobutyroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 41 publications
(48 reference statements)
2
26
0
Order By: Relevance
“…11 Nitrones have been used previously in radical polymerization systems, most notably by Detrembleur and Jêrome, who employed these species to form macronitroxides in situ for subsequent NMP reactions. [12][13][14] The findings of these colleagues during the in situ macronitroxide formation phase are in excellent agreement with recent results from our group.…”
Section: Introductionsupporting
confidence: 89%
“…11 Nitrones have been used previously in radical polymerization systems, most notably by Detrembleur and Jêrome, who employed these species to form macronitroxides in situ for subsequent NMP reactions. [12][13][14] The findings of these colleagues during the in situ macronitroxide formation phase are in excellent agreement with recent results from our group.…”
Section: Introductionsupporting
confidence: 89%
“…To get rid of the uncontrolled formation of PnBuA during the prereaction step, only PBN and AIBN were prereacted in toluene at 85 °C for 4 h. The [PBN]/[AIBN] ratio was fixed to 1/0.5 because it was previously demonstrated to be the optimal one for the styrene radical polymerization with this in situ system 58. After toluene elimination and nBuA addition, the reaction medium was heated at 110 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, we demonstrated that two specific nitrones, that is, N ‐ tert ‐butyl‐α‐isopropylnitrone and PBN (Fig. 3), were able to control the radical polymerization of styrene 57, 58. In contrast to NMP carried out with preformed alkoxyamines, the in situ NMP process based on nitrones is strongly dependent on the experimental conditions, such as the prereaction of the nitrone with a radical initiator before polymerization or not, the prereaction in the presence of the monomer or not, the structures of both the nitrone and the initiator, the nitrone/initiator molar ratio, the time, and the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature there are reports that have demonstrated that automated parallel synthesizers can provide fast and reliable screening possibilities and are well suited for the investigation of various polymerization systems 49. Some of the reported polymerizations are ATRP,50 RAFT,51 NMP,43, 52 cationic ring‐opening polymerization,53 and the synthesis of photocrosslinkable and degradable materials 54. Using ATRP, the polymerization of MMA has been studied after monomer purification 50, 55.…”
Section: Introductionmentioning
confidence: 99%